Fabrication of Graphene‐Oxide (GO)‐Supported Sheet‐Like CuO Nanostructures Derived from a Metal‐Organic‐Framework Template for High‐Performance Hybrid Supercapacitors. Issue 42 (12th November 2018) - Islam, Dewan Azharul; Chakraborty, Anindita; Roy, Atanu; Das, Sachindranath; Acharya, Himadri
Abstract: In this report, graphene oxide (GO)‐supported sheet‐like CuO nanostructures have been fabricated through a novel room temperature method using copper‐based metal‐organic framework (MOF)‐anchored graphene oxides. Copper terephthalate metal‐organic framework (Cu‐(BDC)‐MOF) crystals were synthesized onto the surfaces of exfoliated graphene layers via coordination of the metallic centers with the oxygen functionalities of graphene oxides and terephthalate linkers. The alkaline ageing of the MOF supported graphene oxides in NaOH at ambient temperature leads to the GO/CuO hybrid nanostructures. The morphology and structure of the synthesized materials are examined by X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), transmission electron microscope (TEM) and selected area electron diffraction (SAED). The well‐dispersed sheet‐like CuO nanostructures on graphene oxides show excellent performance in supercapacitor applications.The GO/CuO hybrid nanostructures are capable of delivering a high specific capacitance of 606 F g −1 at scan rate of 2 mV s ‐1 with excellent cycling stability over 93% retention of initial capacitance. Abstract : GO supported sheet‐like CuO nanostructure derived from a metal‐organic‐framework template anchored GO are synthesized at room temperature. The GO/CuO hybrid nanostructure have shown high specific capacitance of 606 F g ‐1 at a scan rate of 2 mV s ‐1, high power densities with a ∼2.0 V operating voltage and excellent recycling stability over 93% of initial capacitance after 1000 cycles.